Counseling on The Utilizing Pineapple Peel Silage as Sheep in Laksana Jaya Group Farmers Ciater Sub-District - Raisman Saiful Mu'min, Achmad; Putra, Kenedy; Riyanti, Lilis (Jurnal Penyuluhan Pertanian, 2023)
The aim of the study was to analyze the level of knowledge and skills of farmers in utilizing pineapple peel silage. Counseling was carried out using the applied study method, lectures, demonstrations, demonstrations and discussions and then analyzed aspects of knowledge and skills through the distribution of pre-test and post-test questionnaires. The target of counseling on members of the Laksana Jaya farmer group was 30 members of the farmer group. Counseling material in the form of an introduction to silage, making pineapple skin silage and sheep farming agribusiness. The instrument was tested for validity and reliability. The results of measuring the knowledge of breeders in utilizing silage technology in the Laksana Jaya farmer group showed a score of 38.96 with the criteria of being quite successful while the skills aspect showed a score of 50% with the criteria of being quite successful. The conclusion is the increasing knowledge and skills of farmers in the utilization of pineapple peels as animal feed silage